Role of agriculture and multifunctional rural development in Serbia - Bogdanov, Natalija; Vasiljevic, Zorica (Applied Studies in Agribusiness and Commerce, 2011)
Serbia is mostly rural country, as three fourth of its territory make rural areas, while almost half population is living in rural areas. Serbian agriculture is the sector which is very important for the total economy of the country in respect of resources, participation in GDP, employment as well as importance for rural areas and population. This is the only sector in Serbian economy that shows positive foreign trade balance in the recent several years.There are potentials for development of agrarian entrepreneurship on one hand, but on the other, there are constraints in existence of great number of small family farms whereas the huge share could not have commercial profile and could not live only from agricultural activities. The concept of multifunctional development of agriculture and rural areas is still present mostly in scientific and political sphere without clear explanation or interpretation as well as mechanisms of implementation. Serbia’s rural space is heterogenic and devastated in different extent, and therefore extremely complicated for planning of multifunctional development.